Coding redundancy controlled data forwarding mechanism in opportunistic networks - Da-peng WU; Peng-wen LOU; Qiao-shou LIU; Yu XIONG; Ru-yan WANG (Tongxin xuebao)
The network coding can improve network transmission efficiency. But most of the data forwarding mechanism does not consider the iteration redundancy control during data transmission. In order to reduce the complexity of decod-ing and iteration redundancy copies sufficiently in coding nodes limited network, the encounter duration estimating method and coding opportunity-aware method are proposed. Further, a data forwarding mechanism for coding redun-dancy control with communication capacity estimating method is designed. It can make full use of the encounter duration between nodes to forward the data, which has more coding opportunity and less than the community capacity. Further-more, the coding number of nodes is updated and the iteration redundancy in every generation is controlled. Experimental results show that, the mechanism could reduce the iteration redundancy in the network and minimize data amount re-quired by decoding, which tends to the theoretical minimum and improves the utilization of network resources.